Computer aided fire safety engineering model based on shortest path algorithm - Gao, Y.; Zhao, J. (Journal of Digital Information Management, 2017)

A survey on data migration management in cloud environment - Hu, L.; Zhao, J.; Xu, G.; Ding, Y.; Chu, J. (Journal of Digital Information Management, 2012)
Cloud computing has become a hot technology. The virtualization technology, one of its core support technologies, is also developing quickly. In recent years, a lot of research and practice have been done in the virtualization field. Live virtual machine migration has drawn much attention as a representative technology of the virtualization field. This paper summarizes the research progress of live virtual machine migration technology including pre-copy, post-copy and CR/TR-Motion analyzes the future research trend.
Keywords: Cloud computing; Live migration; Virtual machine; Virtualization